Activation of proresolving macrophages in dorsal root ganglia attenuates persistent arthritis pain - Silvia Oggero; Mathieu-Benoit Voisin; Francesca Picco; Miguel Á. Huerta; Chiara Cecconello; Thomas Burgoyne; Mauro Perretti; Marzia Malcangio (Proceedings of the National Academy of Sciences, 2025)
Pain independent of disease activity is frequently reported by rheumatoid arthritis patients and remains undertreated. Preclinical evidence suggests that imbalance of neuroimmune proresolving interactions within dorsal root ganglia (DRG) rather than at the site of inflammation plays mechanistic roles in persistent arthritis pain. Here, we inhibited production of proresolving lipid mediators by silencing 12/15-lipoxygenase expression in CX3CR1 + monocyte/macrophages conditional knockout (cKO) mice. In an arthritis model, hind paw mechanical hypersensitivity is exacerbated in male and female cKO mice in association with DRG infiltration of neutrophils, which migrate in response to leukotriene B 4 released by macrophages through 5-lipoxygenase conversion of arachidonic acid provided by neuron-derived vesicles. Neutrophils apoptosis promotes primary macrophage efferocytosis which is defective in cKO macrophages. In wild-type (WT) and cKO mice, intrathecal injection of MerTK activating antibody, attenuates persistent hypersensitivity and polarizes DRG macrophages toward a proresolving phenotype with production of antinociceptive lipoxin A 4 . Thus, we delineate a neuron–macrophage–neutrophil bidirectional circuit that can be exploited to reduce persistent arthritis pain.